The Effectiveness of Learning Interest and Communication Ability on Fikih Learning Outcomes of Students Madrasah Ibtidaiyah Negeri - Zalukhu, Sapran; Arsyad, Junaidi; Hanum OK, Azizah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
Students who are enthusiastic about learning will find it easier to comprehend and apply fiqh teaching material. The enthusiasm of students for independent learning and discovering new information in Fiqh is an indicator. Because there is an attraction for him, students who are interested in a lesson will study it thoroughly. Lessons that are interesting to students are easily remembered. When accompanied by interest, the learning process will run smoothly. This is a quantitative study using the correlational research method, to describe three things: determining the effect of the variable interest in learning (X1) on the variable learning outcomes of Fiqh (Y) students of Madrasah Ibtidaiyah Negeri Nias Utara and looking at the effect of the variable ability to communicate (X2) on the variable learning outcomes of Fiqh (Y) students of Madrasah Ibtidaiyah The study's findings indicate a shared interest in learning and communication skills with the learning outcomes of Fiqh students at Madrasah Ibtidaiyah Negeri Nias Utara. The higher and more positive the students' interest in learning and ability to communicate, the higher and more positive the Fiqh learning outcomes for Madrasah Ibtidaiyah Negeri Nias Utara students, with an effective contribution of 71.4 percent.